Developing a Comprehensive Website for ‘Trending Cakes’: An Analytical Study - Maskar, Vidya; Kulkarni, Mrunali; Dukare, Sakshi; Mundhe, Suhani; Kulkarni, Sanchita (International Journal of Computer Sciences and Engineering, 2024)
The "Trending Cakes Website" aims to be a comprehensive digital solution specifically tailored to enhance and modernize the operations of cake shops. This innovative platform will feature an intuitive interface, allowing users to efficiently handle key tasks such as managing customer orders and accommodating special cake requests with ease and precision. By leveraging cutting-edge technology, the system is meticulously designed to streamline vital business processes, enhance customer satisfaction, and boost overall operational efficiency across various aspects of cake shop management. This forward- thinking solution will empower cake shops to adapt to the evolving needs of contemporary consumers, providing a seamless journey from order placement to delivery that is both efficient and user-friendly for all involved. Ultimately, this digital transformation will fundamentally alter and improve bakery operations in the modern digital era. By embracing this innovative approach, cake shops will be well-equipped to meet customer expectations and thrive in a competitive marketplace, ensuring a delightful experience for all cake enthusiasts everywhere around the world.